Experimental investigation of bridge falsework cuplok joints - André, J. (2011)
Bridge falsework systems are frequently used in the construction, rehabilitation and retrofit of bridge structures. These structures have a significant impact on the cost, construction rate and construction safety of the supported permanent structures. However, the relevant stakeholders often do not consider them as important as permanent structures, and in the recent years a high number of accidents involving bridge falsework systems have been reported. A research programme was initiated aiming to contribute to a better knowledge about the structural behaviour, reliability and robustness of bridge falsework systems. In this paper the results of a series of bending tests of ledger-to-standard Cuplok® joints will be presented and discussed.